Incidencia de la economía peruana en los fondos de pensiones de los trabajadores trujillanos afiliados al sistema privado de pensiones - Alva Carranza, Héctor Enrique (2017)
The purpose of the present investigation is to analyze and explain the effects of the current reduction of national economic growth on the funds of pensioners of trujillo affiliated to the Private Pension System, in order to provide relevant information on this topic of general interest. The scientific method applied in this research is the descriptive - explanatory method since on the basis of the results will establish the characteristics, deficiencies or advantages of each type of pension fund and the propensity of each to vary in its profitability due to the effects of the economic situation, specifying also that such variation is due. It is concluded that the fluctuations in the profitability of the funds managed by the AFPs are caused by the instability of the Peruvian economy as evidenced by economic indicators such as GDP, IGBVL and Foreign Direct Investment and metal prices. These economic values are directly related to the profitability obtained by the pension funds. Also, the investigation, extraction of abstracts, official databases, bibliographic research and journalistic reports were used as techniques and instruments for the collection and processing of data for the results of this thesis.